Answer:
One solution
Step-by-step explanation:
Let's rewrite y = 6 - 3x as y = -3x + 6
Looking at these two equations, we can see they share a y-intercept
Making our solution 6
We know there is only one solution because the equations are not the exact same, if they were we'd have infinitely many solutions
We also know there aren't no solutions because the lines are not parallel (same slopes with difference y-intercepts)
Best of luck
A) The degree of the first term is... 1
![first \ term = 3t](https://tex.z-dn.net/?f=first%20%5C%20term%20%3D%203t%20)
The degree of the second term is... 2
![second \ term = t^2](https://tex.z-dn.net/?f=second%20%5C%20term%20%3D%20t%5E2)
The degree of the third term is... 4
![third \ term = t^4](https://tex.z-dn.net/?f=third%20%5C%20term%20%3D%20t%5E4)
b) The leading term of the polynomial is... 7t⁴
The leading coefficient of the polynomial is... 7
c) The degree of the polynomial is... 4
Answer:
1029.819
Step-by-step explanation:
20.3 * 8.9 * 5.7 = 1029.819
56=2(pi)(r)
r=8.9127
pi(8.9127)^2=249.56cm^2
≈245cm^2 (3s.f.)